An assessment of the evolution of Kenya's solid waste management policies and their implementation in Nairobi and Mombasa: analysis of policies and practices. (October 2017) - Haregu, Tilahun Nigatu; Ziraba, Abdhalah K; Aboderin, Isabella; Amugsi, Dickson; Muindi, Kanyiva; Mberu, Blessing
This paper provides a summary of the priorities and strategies stipulated by the major solid waste management (SWM) policies in Kenya. It also provides a brief assessment of their implementation in Nairobi and Mombasa, drawing on data from a 2016 community-based study. We found that SWM policies have evolved to specificity in terms of focus, functions and scope. There was a shift from criminalizing solid waste action or inaction to promoting good practices; from generic acts to specific ones; and from centralized mandates to more decentralized responsibilities. However, SWM remains a critical concern and a major challenge in Nairobi and Mombasa as a result of weak institutional structures and capacity, weak enforcement of regulatory frameworks, and the control of the sector by criminal cartels.